Activation of cannabinoid type 1 receptor (CB1) modulates oligodendroglial process branching complexity in rat hippocampal cultures stimulated by olfactory ensheathing glia-conditioned medium - Paes-Colli, Yolanda; Trindade, Priscila M. P.; Vitorino, Louise C.; Piscitelli, Fabiana; Iannotti, Fabio Arturo; Campos, Raquel M. P.; Isaac, Alinny R.; de Aguiar, Andrey Fabiano Lourenço; Allodi, Silvana; de Mello, Fernando G.; Einicker-Lamas, Marcelo; de Siqueira-Santos, Raphael; et al. (Frontiers in Cellular Neuroscience, 2023)
The endocannabinoid system (ECS) refers to a complex cell-signaling system highly conserved among species formed by numerous receptors, lipid mediators (endocannabinoids) and synthetic and degradative enzymes. It is widely distributed throughout the body including the CNS, where it participates in synaptic signaling, plasticity and neurodevelopment. Besides, the olfactory ensheathing glia (OEG) present in the olfactory system is also known to play an important role in the promotion of axonal growth and/or myelination. Therefore, both OEG and the ECS promote neurogenesis and oligodendrogenesis in the CNS. Here, we investigated if the ECS is expressed in cultured OEG, by assessing the main markers of the ECS through immunofluorescence, western blotting and qRT-PCR and quantifying the content of endocannabinoids in the conditioned medium of these cells. After that, we investigated whether the production and release of endocannabinoids regulate the differentiation of oligodendrocytes co-cultured with hippocampal neurons, through Sholl analysis in oligodendrocytes expressing O4 and MBP markers. Additionally, we evaluated through western blotting the modulation of downstream pathways such as PI3K/Akt/mTOR and ERK/MAPK, being known to be involved in the proliferation and differentiation of oligodendrocytes and activated by CB1, which is the major endocannabinoid responsive receptor in the brain. Our data show that OEG expresses key genes of the ECS, including the CB1 receptor, FAAH and MAGL. Besides, we were able to identify AEA, 2-AG and AEA related mediators palmitoylethanolamide (PEA) and oleoylethanolamide (OEA), in the conditioned medium of OEG cultures. These cultures were also treated with URB597 10-9 M, a FAAH selective inhibitor, or JZL184 10-9 M, a MAGL selective inhibitor, which led to the increase in the concentrations of OEA and 2-AG in the conditioned medium. Moreover, we found that the addition of OEG conditioned medium (OEGCM) enhanced the complexity of oligodendrocyte process branching in hippocampal mixed cell cultures and that this effect was inhibited by AM251 10-6 M, a CB1 receptor antagonist. However, treatment with the conditioned medium enriched with OEA or 2-AG did not alter the process branching complexity of premyelinating oligodendrocytes, while decreased the branching complexity in mature oligodendrocytes. We also observed no change in the phosphorylation of Akt and ERK 44/42 in any of the conditions used. In conclusion, our data show that the ECS modulates the number and maturation of oligodendrocytes in hippocampal mixed cell cultures.